From Weimar to Hitler : studies in the dissolution of the Weimar Republic and the establishment of the Third Reich, 1932-1934 - Beck, Hermann 1955- HerausgeberIn; Jones, Larry Eugene 1940- HerausgeberIn (Berghahn, 2019)
"Though often depicted as a rapid political transformation, the Nazi seizure of power was in fact a process that extended from the appointment of the Papen cabinet in the early summer of 1932 through the Röhm blood purge two years later. Across fourteen rigorous and carefully researched chapters, From Weimar to Hitler offers a compelling collective investigation of this critical period in modern German history. Each case study presents new empirical research on the crisis of Weimar democracy, the establishment of the Nazi dictatorship, and Hitler's consolidation of power. Together, they provide multiple perspectives on the extent to which the triumph of Nazism was historically predetermined or the product of human miscalculation and intent"--